Some Practical Guidelines for Effective Sample-Size Determination in Observational Studies - Wan Muhamad Amir Wan Ahmad; Wan Abdul Aziz Wan Mohd Amin; Nor Azlida Aleng; Norizan Mohamed (Graduate Program of Syiah Kuala University, 2012)
Abstract- The purpose of this present study was to determine the right sample size in observational study which is focusing on medical or health sciences field. Sample size calculation is actually depends on the type of how the study is designed. For example different formulas are used to calculate the sample size in different type of the study. In this article, the formula of single proportion and two proportions is discussed and an example from medical research, which may contribute to the understanding of this problem, is presented.